Differences in High School Students' Numeracy Literacy Skills through Problem-Based Learning and Discovery Learning Models - Asri, Mawaddah Nur; Maysarah, Siti (Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Negeri Yogyakarta, 2024)
Numeracy literacy skills are essential for students to understand and express quantitative relationships in various real-world contexts. In Indonesia, the literacy level remains low, as indicated by the PISA scores. This study addresses the importance of effective learning models